Predatory journals and their practices present a conundrum for systematic reviewers and evidence synthesisers of health research: A qualitative descriptive study - Pollock, Danielle; Barker, Timothy Hugh; Stone, Jennifer C; Aromataris, Edoardo; Klugar, Miloslav; Scott, Anna M; Stern, Cindy; Ross-White, Amanda; Whitehorn, Ashley; Wiechula, Rick; Shamseer, Larissa; Munn, Zachary (Research synthesis methods, 2024)
Predatory journals are a blemish on scholarly publishing and academia and the studies published within them are more likely to contain data that is false. The inclusion of studies from predatory journals in evidence syntheses is potentially problematic due to this propensity for false data to be included. To date, there has been little exploration of the opinions and experiences of evidence synthesisers when dealing with predatory journals in the conduct of their evidence synthesis. In this paper, the thoughts, opinions, and attitudes of evidence synthesisers towards predatory journals and the inclusion of studies published within these journals in evidence syntheses were sought. Focus groups were held with participants who were experienced evidence synthesisers from JBI (previously the Joanna Briggs Institute) collaboration. Utilising qualitative content analysis, two generic categories were identified: predatory journals within evidence synthesis, and predatory journals within academia. Our findings suggest that evidence synthesisers believe predatory journals are hard to identify and that there is no current consensus on the management of these studies if they have been included in an evidence synthesis. There is a critical need for further research, education, guidance, and development of clear processes to assist evidence synthesisers in the management of studies from predatory journals.
Keywords: predatory journal; průzkumy a dotazníky; Surveys and Questionnaires; predatory publishing; periodika jako téma; Qualitative Research; Periodicals as Topic; Humans; lidé; systematic review; evidence synthesis; methodology; kvalitativní výzkum; qualitative research